2019
DOI: 10.1088/1748-0221/14/03/p03015
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the Hamamatsu R12199-01 HA MOD photomultiplier tube for low temperature applications

Abstract: A: We present a detailed characterisation of the new Hamamatsu R12199-01 HA MOD 3-inch photomultiplier tube (PMT) which is under consideration for the use in segmented optical modules of deep-ice neutrino detectors at the South Pole. Because of the significantly lower operation-temperature range compared to standard applications, a focus of our studies lies on the investigation of the temperature dependence of background characteristics (dark count rate, probability of correlated pulses), timing properties, ga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…In conclusion, the results for both PMT models are in good agreement with the specifications as provided by the manufacturers and show excellent noise behaviour at the low-temperatures relevant for possible use in future IceCube optical modules. More detailed information on the PMT characterization studies can be found in [5] for the Hamamatsu PMTs and in [6] for the HZC Photonics PMTs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In conclusion, the results for both PMT models are in good agreement with the specifications as provided by the manufacturers and show excellent noise behaviour at the low-temperatures relevant for possible use in future IceCube optical modules. More detailed information on the PMT characterization studies can be found in [5] for the Hamamatsu PMTs and in [6] for the HZC Photonics PMTs.…”
Section: Discussionmentioning
confidence: 99%
“…To compensate, the operating voltages of the PMTs were adjusted as a function of temperature in order to keep the PMT gain constant. Figure 6: Gain and operating voltage as a function of temperature for one particular Hamamatsu PMT (left, plot taken from [5]) and a HZC PMT (right).…”
Section: Temperature-dependent Pmt Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…a reduced overall tube length of 91 mm. The main characteristics of the R15458-02 model were not affected by the reduced length and are comparable to the R12199-01 HA MOD, which was characterized in detail in [7]. The PMTs come equipped with an active base (see Sec.2.2) by the manufacturer, with the PMT-base compound referred to as R15458-20.…”
Section: Photomultipliersmentioning
confidence: 97%
“…As conductive objects at non-photocathode potential close to the photocathode of a negatively fed PMT tend to evoke high and unstable dark-noise rates [5] the reflectors will be connected to photocathode potential via dedicated copper strips (see left picture in Fig. 3).…”
Section: Photomultipliers and Reflectorsmentioning
confidence: 99%